FUNGSI SISTEM INFORMASI AKUNTANSI DALAM MENINGKATKAN EFISIENSI DAN EFEKTIVITAS PELAPORAN KEUANGAN PADA BADAN USAHA MILIK DAERAH PROVINSI SUMATERA UTARA - LUNA THERESIA TAMBUNAN (LP2MTBM MAKARIOZ, 2020)
Information systems for management facilitate their tasks effectively and efficiently. Effective means a measure of the level of use of resources in a process. The less use of resources, the more efficient the process. Efficient processes are characterized by process improvements, making them cheaper and faster. Whereas efficient means a measure of the level of fulfillment of output or process objectives.The higher the achievement of targets or process objectives, the process is said to be more effective. An effective process is characterized by process improvement, so that it becomes better and safer. Accounting information systems can collect, classify, process, analyze and communicate financial information, thereby helping companies launch business activities therein.